The effects of brand experience, trust and satisfaction on building brand loyalty - an emphasis study of cosmetic brands in Klang Valley / Nur Syafiqah Aqilah Mohamad Hasim and Saidatul Karimah Zakaria - Mohamad Hasim, Nur Syafiqah Aqilah; Zakaria, Saidatul Karimah (Faculty of Business and Management, 2016)
The purpose of this research was to determine the relationship between brand experience, satisfaction, trust and brand loyalty towards cosmetic brands in Klang Valley. There were four main objectives in this research: 1) to determine whether brand experience has significant relationship with brand loyalty, 2) to determine whether trust has significant relationship with brand loyalty, 3) to determine whether satisfaction has significant relationship with brand loyalty and 4) to determine the variable that has most significant relationship with brand loyalty. The quantitative research approach was employed in this study as a research design. The study samples 258 female consumers of cosmetic brands in Klang Valley as the case study. Data analysis for this study was conducted using SPSS (Statistical Package for the Social Sciences) software. The analysis used descriptive statistics such as mean, frequency, percentage and standard deviation, as well as correlation analysis and regression analysis to facilitate meaningful analysis. The findings indicated that there were significant relationships between brand experience, trust, satisfaction and brand loyalty.